Constraining the nature of DG Tau A's thermal and non-thermal radio emission. Issue 4 (3rd October 2018) - Purser, S J D; Ainsworth, R E; Ray, T P; Green, D A; Taylor, A M; Scaife, A M M
Abstract: DG Tau A, a class-II young stellar object (YSO), displays both thermal and non-thermal radio emission associated with its bipolar jet. To investigate the nature of this emission, we present sensitive ($σ \sim 2\, {\rm μ Jy}\, beam^{-1}$ ), Karl G. Jansky Very Large Array (VLA) 6 and $10\, {\rm GHz}$ observations. Over $3.81\, {\rm yr}$, no proper motion is observed towards the non-thermal radio knot C, previously thought to be a bowshock. Its quasi-static nature, spatially resolved variability, and offset from the central jet axis support a scenario whereby it is instead a stationary shock driven into the surrounding medium by the jet. Towards the internal working surface, knot A, we derive an inclination-corrected absolute velocity of $258± 23{ \rm \, {\rm km}\, {\rm s}^{-1}}$ . DG Tau A's receding counterjet displays a spatially resolved increase in flux density, indicating a variable mass-loss event, the first time such an event has been observed in the counterjet. For this ejection, we measure an ionized mass-loss rate of $(3.7± 1.0) × 10^{-8}\, {\rm M_{\odot }}\, {\rm yr}^{-1}$ during the event. A contemporaneous ejection in the approaching jet is not seen, showing it to be an asymmetric process. Finally, using radiative transfer modelling, we find that the extent of the radio emission can only be explained with the presence of shocks, and therefore reionization, in the flow. Our modelling highlights the need to consider the relative angular size of optically thick, and thin, radio emission from a jet, to the synthesized beam, when deriving its physical conditions from its spectral index.